Evaluation of mandibular functional limitation in patients with temporomandibular joint disorders and the relationship with other psychosocial factors - Nguyen Ngoc Hoa; Toan Do; Tran Thai Binh; To Thanh Dong; Tran Thi Minh Quyen; Viet Hai Hoang (PLoS ONE, 2025)
Introduction Temporomandibular joint disorders (TMDs) are a common source of orofacial pain and dysfunction, often characterized by myalgia, restricted mouth opening, and limitations in mandibular movement. This study aims to evaluate the extent of mandibular functional limitation across different TMD subgroups and its relationship with anxiety and depression. Methods A cross-sectional descriptive study was conducted on 120 patients diagnosed with temporomandibular joint disorders according to the Diagnostic Criteria for TMDs (DC/TMD). Participants completed self-report questionnaires assessing the Jaw Functional Limitation Scale-8 (JFLS-8), Visual Analog Scale (VAS), Patient Health Questionnaire-9 (PHQ-9), General Anxiety Disorder-7 (GAD-7), Graded Chronic Pain Scale (GCPS), and Oral Behaviors Checklist (OBC). The Mann-Whitney U and Kruskal-Wallis tests were used to compare means between groups for non-normally distributed data. The relationship between JFLS-8 and other variables was assessed using linear regression. Statistical significance was set at p < .05. Results Chewing hard foods is the most affected activity in the arthralgia group (7.25 ± 1.91), while swallowing is the least affected activity (0.13 ± 0.35). Statistically significant differences were found among TMJ disorders for chewing tough food, chewing chicken, opening wide enough to drink from a cup, and yawning ( p < .05). Disc displacement without reduction, with a limited opening subgroup, exhibited the highest JFLS-8 scores for chewing and mouth-opening-related activities. JFLS-8 is correlated with the PHQ-9, GAD-7, GCPS ( p < .05). Conclusions Significant variations in mandibular functional limitation were observed across TMD subgroups. The severity of these limitations demonstrated a positive correlation with levels of depression, anxiety, and chronic pain.